Trabajo desde casa e inclusión laboral. Bases del salario emocional y factores determinantes en el clima organizacional (2018)
It is said that the customer is the raison d'être of the companies, so the employee has been left aside. This one plays a very important role in the organizations since it is the letter of presentation of the same and of this will depend the fulfillment of the objectives. It is very important to take into account that the gaps that exist, physically or mentally in a worker must be eliminated, provided that it demonstrates the relationship between knowledge and commitment to the organization they represent. The employee, his tastes, passions, interests and family, are important in the companies, and the feeling of being part of an organization that cares for this and for everything that surrounds it, is one of the factors so that, Develop functions to increase productivity